La protection de la forêt tropicale à l’heure de l’intégration : de la transformation des sols à la transformation des paysans - Carmen Pedroza (Cahiers des Amériques Latines)
This paper is part of a research project on Mexican tropical forest management and the impacts of development policies on this territory. We are taking into account the evolution of natural ressource conservation and development policies in relation to global change. Our case study is Calakmul, in the State of Campêche, Mexico, a municipality and a natrual protected area considered to be the largest in Mexico and one of the most important in the world because of its biodiversity richness and its archeological zones.